PENGARUH KOMITMEN ORGANISASIONAL, MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KEBUDAYAAN DAN PARIWISATA PROVINSI JAWA TENGAH - Mochamad Rahidin Syakur, 10.05.51.0047; Wanuri, Wanuri (Students Journal of Economic and Management, 2014)
This study aims to analyze the influence of motivation, organizational commitment, and organizational culture on the performance of employees at the Department of Culture and Tourism of the Province of Central Java. The sample in this study was 60 respondents. The sampling method used was judgment sampling, which is one type of purposive sampling. Method of data collection by questionnaire and interview. Engineering test data used in this study include testing the validity of the factor analysis, reliability test with Cronbach alpha. Classical assumption test, multiple linear regression analysis, t-test to test and prove the research hypothesis. The success of an organization is determined by the performance of the employees themselves, from the performance of the employee motivation membeikan need for passion and satisfaction in the work of employees. Keywords: Organizational Commitment, motivation, Job Satisfaction and Employee Performance